Trials and Justice in Awaara: A Post-Colonial Movie on Post-Revolutionary Screens? - Alison W. Conner (Law Text Culture, 2014)
Perhaps surprisingly, one of the most popular Chinese movies of all time is actually an Indian film. Filmed in 1951 in newly independent India, Awaara (The Vagabond) was released in China after the official introduction of the opening and reform policies in 1979, when the country embarked on its current post-socialist, post-revolutionary course. Known as Liulangzhe in China, Awaara received a rapturous response from Chinese audiences and even now everyone over a certain age remembers watching the movie. Thanks to the Internet, many younger Chinese have also seen Awaara, sometimes dubbed in Chinese (I first saw it dubbed in Chinese myself), or if they haven’t seen it they can tell you why their parents and grandparents loved it so much.